CERTIFICATION CRITERIA MATRIX FOR EXPERT RATING OF PROFESSIONAL SERVICES - Jegere, Sarmite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the Latvian certification system of individuals, there is necessary to ensure appropriate process realization in the interests of public protection and government needs, which gets incorporated into the EU common structure. An assessment of the certification system and its institutional structure is done with the aim to develop proposals for the improvement of the Latvian certification system for reducing costs, while ensuring both high system efficiency and recipients services and the public interest. To achieve its goals, the research study provided a summary of the situation in Latvia, as well as in the neighbouring countries: Lithuania, Poland, Estonia and Finland. During the research study, there were used both the secondary and the primary sources of information. Primary research was carried out in Latvia and consisted of two parts: expert interviews and focus groups. The results of the research are guidance to the overall approach and the criteria by which to guide one in the future, for setting which professional service providers require a mandatory certification. A matrix was made in the process of the research, which helps to define a certified profession, taking into account the need to protect the public interest and the level of national involvement in the regulation of specific areas of professional services.